Assesstment of soil organic carbon in mangrove area, Pante Bayam- Aceh - Harefa, Meilinda Suriani; Eling Tuhono; Zulkifli Nasution; Arida Susilowati; Rifqi Ulfah Nikmah; Fitra Yuda Pratama (Talenta Publisher, 2025)
Pante Bayam is one of natural mangrove area in Aceh Province. Due toanthropogenic activities such as fishpond, the area become degradated. This studyaims to analyze soil organic carbon (SOC) stock based on soil depth and texturecharacteristics at several observation points in the study area. Data were collectedfrom seven sample locations with four categories of soil depth: 0–15 cm, 15–30cm, 30–50 cm, and 50–100 cm. The results showed that the highest carbon stockwas found at a depth of 50–100 cm, reaching 159.1 Mg C/ha, while the 15–30 cmlayer had the lowest carbon stock. This indicates that the subsoil plays a significantrole in long-term carbon storage. The distribution of carbon stocks also variedbetween locations, where PB04 and PB07 showed the highest values, while PB05and PB06 showed the lowest. Correlation analysis showed a positive relationshipbetween clay content and soil carbon stock, indicating that fine soil texturesupports carbon accumulation through the formation of stable aggregates. Thesefindings emphasize the importance of soil management that considers soil depthand physical characteristics to increase the potential for climate change mitigationthrough sustainable soil carbon storage